Nutritional Composition and Histopathological Effects of Composite Biscuits Made From Finger Millet, Soybean, and Wheat Bran on Albino Wistar Rats (IPS Journal of Nutrition and Food Science, 2025)
Biscuits are snacks consumed in between meals. Biscuit was produced from composite flour (finger millet flour, soybean flour, and wheat bran). Five samples; FSW1 (60% finger millet flour, 35% soybeans flour and 5% wheat bran) FSW2 (70% finger millet flour, 25% soybeans flour and 5% wheat bran) FSW3 (80% finger millet flour, 15% soybeans flour and 5% wheat bran) FSW4 (90% finger millet flour, 5% soybeans flour and 5% wheat bran) FSW5 (100% finger millet) of biscuit were produced from the composite flour and FSW6 (positive control). This study highlights the potential of finger millet, soybean flour, and wheat bran blends for the production of nutritious biscuits. Proximate composition biscuit and histopathology of Wistar rats were carried out. Proximate analysis showed increasing soybean flour content significantly increased protein (5.67-14.92%) and fat (19.65-26.59%) levels, moisture content reduced with values between (2.28-6.32%) and carbohydrate between (38.20-55.64%). Crude fiber ranged from 11.74-16.66%, with wheat bran contributing to higher values. Biscuits from the composite flours were fed to albino Wistar rats for 28 days before histopathological examination. Kidney histology showed no significant changes related to the feed composition, with some formulations displaying a nearly normal architecture. Liver histology revealed normal to nearly normal hepatic structure in most of the groups, with some sinusoidal dilation and diffusion. The heart histology indicated varying degrees of change, including connective tissue enlargement, muscle fiber changes, and lipid deposits in some formulations. The biscuit will provide a good source of protein and because of the high fiber content, it will aid digestion.
Keywords: Composite Flour; Biscuit; Finger Millet; Soybean; Histopathology; Nutritional Quality; Wistar Rats